Romantic trends in women's image in poet diaspora - Hleel, Alaa Sadiq (2014)
In this study, the researcher investigated the woman’s image in the Mahjar poetry. The woman’s image in the Mahjar poets’ work took a new trend of expression as the Mahjar poets were influenced by the Romantic Movement which considered women as an essential representation in expressing their principles and rules. That influence was clearly shown in the Mahjar poetry. This study aimed at illustrating the new features of the woman’s image that appeared in the Mahjar poets’ work. Moreover, this study explored the new meanings and significant features the woman’s image could indicate in the Mahjar poetry. Further, this study aimed at highlighting the differences between woman’s images for the northern and southern Mahjar poets and their creativity in illustrating the literary and poetic image of woman apt to their purposes. This study utilized three research approaches. Top of which was the inductive approach which helped the researcher to inductively investigate and track the poets’ background and lives, and the woman’s image in their poetry. The second method was the analytic approach through which meanings and significance in the woman’s image were explored. The third method was the comparative approach through which the researcher managed to identify the similarities and differences in the woman’s image in the northern and southern Mahjar poets’ work. Adopting the three research approaches led to achieving the objectives of this study. The results reached in this study showed that the Mahjar poets were influenced by the Romantic Movement in illustrating woman in a way that reflected the real life issues and problems. It was also found that there was a significant difference between the northern and southern Mahjar poets in illustrating the woman’s image either through imagination or through real life techniques. Moreover, there were differences between the poets in presenting meanings and significant features of the woman’s image.